2015
DOI: 10.3109/14767058.2015.1017460
|View full text |Cite
|
Sign up to set email alerts
|

Social media messaging in pregnancy: comparing content of Text4baby to content of free smart phone applications of pregnancy

Abstract: To improve content without increasing text message number, Text4baby could replace messages on recruitment with messages regarding normal pregnancy symptoms, fetal development and postpartum contraception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…There were four apps on guidelines, the RCOG guideline app was paid while other three were free apps. In the past points have been made about contraception, use of social media & apps on Pregnancy [2][3][4][5], but present study revealed much wider applications of the apps in the field of Obstetrics & Gynecology. Limitation of the study is the fact that it has not looked at all the operating system app stores & hence has info on the two most utilized app stores.…”
Section: Resultsmentioning
confidence: 69%
“…There were four apps on guidelines, the RCOG guideline app was paid while other three were free apps. In the past points have been made about contraception, use of social media & apps on Pregnancy [2][3][4][5], but present study revealed much wider applications of the apps in the field of Obstetrics & Gynecology. Limitation of the study is the fact that it has not looked at all the operating system app stores & hence has info on the two most utilized app stores.…”
Section: Resultsmentioning
confidence: 69%
“…Only 7of these articles [16,18,20,26-30] represented actual studies; the others described the program [3,4,17,31] or described a study that was going to take place [19,23]. Of the 7 that described actual studies, 2 focused on the American military population [16,28], 1 was a pilot study [18], 2 focused on the health literacy of Text4Baby participants [26,27], and 2 focused on the content of the messages [20,29]. …”
Section: Resultsmentioning
confidence: 99%
“…Lewkowitz and colleagues produced first a conference abstract and then a paper comparing the content of Text4Baby messages with messages from other pregnancy apps, such as the one sponsored by the American College of Obstetrics and Gynecology and March of Dimes [20,29]. Their analysis suggested that Text4Baby could improve by decreasing the number of messages about obtaining medical care and increasing the number of messages about healthy eating, normal weight gain, exercise, and nutrition without increasing the overall number of messages [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations